أستاذ غلام أعظم ومساهمته في إصلاح المجتمع البنغلاديشي - Muhiuddin Khandokar Arif Muhammad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The largest and busiest Islamic political organization in Bangladesh is thought to be the Islamic Renaissance Movement. Ghulam Azam orchestrated and oversaw it until recently. This research makes an effort to examine the group's policies by citing Ghulam Azam, reading his history, and demonstrating his influence on both Western and Islamic education as well as their influence on his political actions. Concentrating on some of his concepts and contributions, evaluating them in the context of current social and political conditions in Bangladesh, and then looking at the place of the Islamic community in relation to those conditions. However, the group's leadership occasionally made statements that infuriated the national forces and furthered the gulf between the group and the populace, such as: “We did not make mistakes in 1971 AD.” It is unclear how Ghulam Azam and the new group's leadership will handle these issues going forward.